Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.5455/javar.2017.d222
|View full text |Cite
|
Sign up to set email alerts
|

Livestock associated epidemiological information profiling in New Sandwip Island (Jahajerchar) of the Meghna estuary, Noakhali using participatory disease searching tool

Abstract: Objective: The present study was conducted in New Sandwip island (Jahajerchar) of the Meghna estuary, Noakhali to explore animal species are being reared, their disease status, and also to finding out the constraints and opportunitities for keeping livestock in the island. Materials: Considering local knowledge as an epidemiological intelligence, the livestock species and their disease profile as well as livestock keeping problems were assessed through two focus group discussion with informants' interview usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The mixed grazing and housing of both young and adult animals gave them a higher chance to be infected with those parasites through cross-contamination. However, Islam et al (2017b) found a higher prevalence in young animals whereas, Rahman et al (2017) and Singh et al (2017) found a higher frequency in adults. Grazing, housing and managemental practices could be the reasons of such variation (Hassan et al 2011;Dey et al 2020).…”
Section: Discussionmentioning
confidence: 78%
“…The mixed grazing and housing of both young and adult animals gave them a higher chance to be infected with those parasites through cross-contamination. However, Islam et al (2017b) found a higher prevalence in young animals whereas, Rahman et al (2017) and Singh et al (2017) found a higher frequency in adults. Grazing, housing and managemental practices could be the reasons of such variation (Hassan et al 2011;Dey et al 2020).…”
Section: Discussionmentioning
confidence: 78%